Integrating Network Pharmacology and Component Analysis Study on Anti‐Atherosclerotic Mechanisms of Total Flavonoids of Engelhardia roxburghiana Leaves in Mice. Issue 3 (30th January 2020) - Wei, Jie; Zhang, Ying; Li, Dongmei; Xie, Tanggui; Li, Yanjing; Li, Jia; Chen, Xiaojun; Wei, Guining
Abstract: Engelhardia roxburghiana Wall . leaves are widely used to develop herbal teas in southeast of China due to medicinal use for diabetes mellitus and hyperlipidemia. Studies have demonstrated that the total flavonoids of E. roxburghiana leaves (TFER) exhibited regulatory effects on blood glucose and lipids. To clarify the active ingredients of TFER and their targets in treating atherosclerosis, the present study integrated chemical analysis, network pharmacology analysis and animal experimental studies. Firstly, high performance liquid chromatography‐mass spectrometry/mass spectrometry (HPLC/MS/MS) was utilized to identify components of TFER. Then, active ingredients were screened by oral bioavailability (OB) and drug‐likeness (DL) index. Thirdly, network was constructed to predict major targets of active ingredients against atherosclerosis. Finally, to verify parts of predicted signaling, Apoe −/− mice were used to develop atherosclerosis. Atherosclerotic plaques in aorta were evaluated by echocardiography. Then, serum lipids, target genes expressions in thoracic aorta were determined by qRT‐PCR and ELISA methods. Chemical analysis revealed 10 components in TFER sample, 7 of which acted as active ingredients, including naringenin, kaempferol, quercetin, isoengeletin, engeletin, astilbin and quercitrin. KEGG pathway analysis highly enriched in some inflammatory signalings, including NF‐ κ B signaling, Toll‐like receptor signaling and TNF signaling. The animal studies indicated that TFER reduced atherosclerotic plaques size in aorta and significantly decreased the serum lipids, down‐regulated NF‐ κ B signaling by decreasing mRNA level of NF‐ κ B p65 subunit, TNF‐ α and VCAM‐1, as well as IL‐1 β expressions in thoracic aorta, eventually alleviating atherosclerosis progression, which was in consistent with our prediction. Abstract :